‘With certain grand Cottleisms’: Joseph Cottle, Robert Southey and the 1803 Works of Thomas Chatterton. - Groom, Nick (Romanticism, 2009)
The article presents an historical overview of the publication of the "Complete Works of Thomas Chatterton," by Robert Southey and Joseph Cottle in 1803. Details are given describing the popularity of Catterton's works during the period and accounts of Cottle's and Southey's particular work on his posthumous works are provided. The literary research, selection and editing, and efforts to obtain publishing rights to Catterton's works by the two are described in depth, citing several letters and other primary documents discussing their project.